Profile and anticoagulation outcomes of patients on warfarin therapy in an urban hospital in Cape Town: a review of records of patients attending Victoria Hospital, Cape Town, South Africa - Sonuga, Babatunde (Department of Public Health and Family Medicine, 2016)
Background: Warfarin is the most frequently used oral anticoagulant worldwide and it is the oral anticoagulant of choice in South Africa for reducing thrombosis - related morbidity and mortality. However, the safety and efficacy of warfarin therapy depends mainly on careful monitoring and maintenance of the international normalized ratio (INR) within an optimal therapeutic range. In the ACTIVE - W trial conducted across nine countries, South Africa had the poorest anticoagulation control with warfarin. This study showed that 86% of patients on warfarin therapy in the country have their mean time in therapeutic range below target. This was an indication of a very poor warfarin control in South Africa .The trial reported centre - specific differences within each country. It was however silent on these differences in South Africa. Aim: The aim of this study was to describe the profiles and the anticoagulation outcomes of patients on warfarin therapy in a major warfarin clinic in Western Cape Province of South Africa. Setting: Victoria Hospital - a district hospital in Cape Town, South Africa, which serves around one million people. Methods: A cross sectional review of clinical records of patients on warfarin therapy who attended the INR clinic from 01 January 2014 to 30 June 2014 was done. Data analysis was done with Stata to generate appropriate descriptive data and groups were compared using non - parametric tests. Results: Age range for male patients was between 29 - 85 years with median age of 62 years, while that of female patients was between 17 - 92 years with a median age of 66 years. Atrial fibrillation (AF) was the commonest indication for warfarin use in this study and hypertension was the commonest co-morbidity amongst these patients. Only 48.5% (66 patients) achieved target therapeutic range as of 01 July 2014, while 51.5% (70/136) of the patients were out of range. Patients who were non - alcohol users (88.9%) had better therapeutic control than those who consumed alcohol (9.6%). There was a significant association between alcohol consumption and poor anticoagulation outcomes (p value <0.022). Unlike alcohol use, there was no statistical relationship between smoking habit and target therapeutic range (P value = 0.198). The study also showed that anticoagulation outcomes were better among the older age groups, male patients and in those with atrial fibrillation. The prevalence of thrombotic events while on warfarin treatment was 2.2%, while prevalence of haemorrhagic events was 14%. Most of the patients with bleeding events were on concurrent use of warfarin and other medications with potential drug interactions. Conclusion: In this study, patients who achieved target therapeutic control were less than the acceptable 60%. Bleeding complications were more common among patients on concurrent use of warfarin with other medications such as NSAIDS and simvastatin. Therefore, it is of utmost importance for health professionals to take note of drug - drug or drug - disease interactions among patients on warfarin and to monitor INR levels more frequently in patients who have to unavoidably be on concurrent use of medications with possible major interactions with warfarin. Keywords: Oral anticoagulant, anticoagulation outcomes, therapeutic control, percentage INR within target therapeutic range (%ITTR).